2017
DOI: 10.18632/oncotarget.22962
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous detection of genetic and copy number alterations in BRCA1/2 genes

Abstract: Germline mutations in BRCA1 and BRCA2 genes (BRCA1/2) predispose to hereditary breast and ovarian cancer syndrome (HBOC), and their dysregulation increases the risk of cancers. The detection of pathogenic BRCA1/2 variants is essential for the diagnosis and prevention of HBOC, and for offering treatment decisions for patients. Therefore, there is a growing demand for the development of accurate, rapid assay systems that simultaneously detect pathogenic variants and copy number alterations. Here, we tested Therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…It is considered as an alternative assay to investigate both types of BRCA1/2 genetic alterations in one workflow. This panel efficiency has been investigated by Hirotsu et al (2017) [ 34 ], and according to his study results, the Oncomine BRCA1/2 research assay panel is a highly accurate tool for analyzing variants with wide-ranging allelic fractions and for detecting copy number alterations.…”
Section: Discussionmentioning
confidence: 99%
“…It is considered as an alternative assay to investigate both types of BRCA1/2 genetic alterations in one workflow. This panel efficiency has been investigated by Hirotsu et al (2017) [ 34 ], and according to his study results, the Oncomine BRCA1/2 research assay panel is a highly accurate tool for analyzing variants with wide-ranging allelic fractions and for detecting copy number alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed a better performance of the Oncomine™ BRCA Research assay compared with the Ion Ampliseq™ BRCA Panel in terms of ability to identify deletions at homopolymer sites, on target mapped reads, reduction of low-quality mapped reads and false-negative results. In the same study, using the Oncomine Panel a large deletion was identified, subsequently confirmed by MLPA [ 31 ]. The NGS-CNV analysis requires a complete validation of the "baseline", which is crucial to obtain accurate and reliable results for clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer susceptibility genes 1 and 2 ( BRCA1 and BRCA2 ) are tumour suppressor genes that maintain genomic integrity 1 2. Mutations in BRCA1 and BRCA2 lead to defective double-stranded DNA repair, dysregulation of the cell cycle and chromosomal aberrations 3–6.…”
Section: Introductionmentioning
confidence: 99%